2017
DOI: 10.3390/ijerph14070816
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Air Pollution on Menstrual Cycle Length—A Prognostic Factor of Women’s Reproductive Health

Abstract: Air pollution can influence women’s reproductive health, specifically menstrual cycle characteristics, oocyte quality, and risk of miscarriage. The aim of the study was to assess whether air pollution can affect the length of the overall menstrual cycle and the length of its phases (follicular and luteal). Municipal ecological monitoring data was used to assess the air pollution exposure during the monitored menstrual cycle of each of 133 woman of reproductive age. Principal component analyses were used to gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 89 publications
1
22
0
1
Order By: Relevance
“…A high concentration of PM directly reduces the visibility of air. It is also well known that PM severely damages public health [22][23][24]. For the Chinese population, Lu et al [25] found that short exposures to PM 2.5 and PM 10 were positively associated with increases in mortality due to cardiovascular and respiratory disease.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A high concentration of PM directly reduces the visibility of air. It is also well known that PM severely damages public health [22][23][24]. For the Chinese population, Lu et al [25] found that short exposures to PM 2.5 and PM 10 were positively associated with increases in mortality due to cardiovascular and respiratory disease.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Others might be variations of the normal physiological process. In addition, some authors have outlined the impact of environmental factors such as air pollution ( 10 ) or light pollution ( 11 ) that deserve specific attention due to their seemingly great impact on the physiology of reproduction ( 12 ). We have noticed that the relationships between a small maximum follicle size and a short luteal phase or a low mPDG are not maintained when the regression is adjusted for the general characteristics of the women; thus, small follicles and luteal deficiencies might be the consequences of an underlying characteristic.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, female fertility and reproductive health are sensitive to toxic exposure, specifically to endocrine disruptor pollutants [13], and have long-term adverse effects. However, several studies have analyzed the connection between environmental air pollution and female reproductive competence, suggesting an adverse linkage between fertility and toxicants [14].…”
Section: Introductionmentioning
confidence: 99%